The Major Target of the Endogenously Generated Reactive Oxygen Species in Response to Insulin Stimulation Is Phosphatase and Tensin Homolog and Not Phosphoinositide-3 Kinase (PI-3 Kinase) in the PI-3 Kinase/Akt Pathway - Seo, Ji Hae (The American Society for Cell Biology, 2005)
Phosphoinositide-3 kinase (PI-3 kinase) and its downstream signaling molecules PDK-1 and Akt were analyzed in SK-N-SH and SK-N-BE(2) human neuroblastoma cell lines. When cells were stimulated with insulin, PI-3 kinase was activated in both cell lines, whereas the translocation of PDK-1 to the membrane fraction and phosphorylated Akt were observed only in SK-N-SH cells. Analyses of the insulin-mediated reactive oxygen species (ROS) generation and Phosphatase and Tensin homolog (PTEN) oxidation indicate that PTEN oxidation occurred in SK-N-SH cells, which can produce ROS, but not in SK-N-BE(2) cells, which cannot increase ROS in response to insulin stimulation. When SK-N-SH cells were pretreated with the NADPH oxidase inhibitor diphenyleneiodonium chloride before insulin stimulation, insulin-mediated translocation of PDK-1 to the membrane fraction and phosphorylation of Akt were remarkably reduced, whereas PI-3 kinase activity was not changed significantly. These results indicate that not only PI-3 kinase activation but also inhibition of PTEN by ROS is needed to increase cellular level of phosphatidylinositol 3,4,5-trisphosphate for recruiting downstream signaling molecules such as PDK-1 and Akt in insulin-mediated signaling. Moreover, the ROS generated by insulin stimulation mainly contributes to the inactivation of PTEN and not to the activation of PI-3 kinase in the PI-3 kinase/Akt pathway.